On the extremal extensions of a non-negative Jacobi operator - Goloshchapova, N.; Ananieva, A. (Methods of Functional Analysis and Topology, 2013)
We consider the minimal non-negative Jacobi operator with p× p-matrix entries. Using the technique of boundary triplets and the corresponding Weyl functions, we describe the Friedrichs and Krein extensions of the minimal Jacobi operator. Moreover, we parametrize the set of all non-negative extensions in terms of boundary conditions.